DETEKSI ZONA MINERALISASI EMAS DI GUNUNG GUPIT, MAGELANG MENGGUNAKAN METODE INDUCED POLARIZATION: DETECTION OF GOLD MINERALIZATION ZONES IN GUNUNG GUPIT, MAGELANG USING INDUCED POLARIZATION METHOD - Yatini; Zakaria, Muhammad Faizal; Putri, Rizkia; Zakaria, Suharwanto (Universitas Trisakti, 2024)
Mount Gupit is an area with gold mineralization potential which is part of the Menoreh Mountains, in the Magelang area. Mineralization potential mapping was carried out using geophysics, namely the Induced Polarization method. Induced Polarization Method measurements were carried out in 5 trajectories in a relatively west to east direction and with varying path lengths. The configuration used is a dipole-dipole configuration with a: 10 meters and n: 1-6. Interpretation is carried out on the results of the Resistivity and Chargeability data inversion. The inversion results show a resistivity range from 2 to 400 Ohm-m. Resistivity values are divided into three criteria, namely low with a value of less than 10 Ohm-m as clay rock, medium with a range of (10-75) Ohm-m as pyroclastic breccia and high with a value greater than 75 Ohm-m as intrusion or chunks of andesite. The inversion results show that the chargeability value varies from 2 to 80 ms. This value is divided into three criteria, namely low (<10 ms), medium (10 to 35) ms and high (>35 ms). Low chargeability values are interpreted as zones that are not mineralized so that there are no metal minerals. The mineralized zone is being interpreted from a moderate chargeability value. Meanwhile, a high chargeability value is interpreted as a zone that is strongly mineralized and contains significant metallic minerals. The existence of a mineralized zone stretches from track 2 to track 5 to the north, while the zone has disappeared or been exhausted in track 1 to the south of the research area.